1997
DOI: 10.1111/j.1525-1446.1997.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors: Interaction Effects on Health‐Promoting Behavior and Health Related Factors

Abstract: The purpose of this study was to examine the main and interaction effects of race, gender, and education on health-promoting behaviors, problem solving appraisal, health value, and health definition. Using a convenience sample of 331 employees, a series of three-way ANOVAs were performed. Only gender exerted main effects on health-promoting behaviors, including exercise, relaxation, and health promotion. No interaction effects were presented. Neither main nor interaction effects were found for approaching prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
4
21
1
Order By: Relevance
“…No gender differences in self-care agency were found by this study. This result is in contrast to the findings in the literature which suggest that men and women tend to engage in different health-promoting behaviors 54,55 . It is possible that gender differences were not found because the ASAS-R only assesses level of self-care capacity and not specific behaviors.…”
Section: Asas-r Swlscontrasting
confidence: 99%
See 1 more Smart Citation
“…No gender differences in self-care agency were found by this study. This result is in contrast to the findings in the literature which suggest that men and women tend to engage in different health-promoting behaviors 54,55 . It is possible that gender differences were not found because the ASAS-R only assesses level of self-care capacity and not specific behaviors.…”
Section: Asas-r Swlscontrasting
confidence: 99%
“…with a higher education level are likely to have a greater awareness of the benefits of self-care and have greater access to information on selfcare 52 . For example, empirical studies provide evidence that individuals with a lower level of education are more likely to smoke, be obese and be physically inactive than individuals with higher levels of education 53,54 . It is also important to note that people with higher levels of education and income are generally older and therefore the relationship between these variables may be tangential.…”
Section: Asas-r Swlsmentioning
confidence: 99%
“…Felton, Parsons, Bartoces, 1997;Neal, 1983). Neal found that individuals with higher levels of education possessed more positive problem-solving appraisal.…”
Section: Problem-solving Inventorymentioning
confidence: 99%
“…The factors determining health-enhancing behaviours have been investigated elsewhere (Duffy 1997;Felton et al 1997;Pullen et al 2001;Qi et al 2006;Beser et al 2007). The relationship between age and the likelihood of participating in health-enhancing lifestyle is inconclusive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of gender on health-enhancing lifestyle seems to be contradictory. Felton et al (1997) draw on a survey data and find that females have higher odds of engaging in health-enhancing lifestyle than males. Similar findings are evidenced by a more recent study by Paulik et al (2010).…”
Section: Literature Reviewmentioning
confidence: 99%